Impact of a “Digital Health” Curriculum on Students’ Perception About Competence and Relevance of Digital Health Topics for Future Professional Challenges: Prospective Pilot Study - Juliane Kröplin; Leonie Maier; Jan-Hendrik Lenz; Bernd Romeike (JMIR Formative Research)
Abstract BackgroundThe rapid integration of digital technologies in health care has emphasized the need to ensure that medical students are well-equipped with the knowledge and competencies related to digital health. ObjectiveThis study aimed to evaluate the impact of the “Digital Health” curriculum at our university on the perceptions of medical students regarding the relevance of digital health topics for their future professions and their self-assessed competence in these areas. MethodsThe “Digital Health” curriculum was introduced at a German university for 2 consecutive semesters. The perceived relevance of topics for their future careers and their subjective competence were evaluated before and after the curriculum using a Likert scale. Furthermore, the practical gamification-based teaching part of the robotics teaching unit was evaluated. In total, 6 months after completing the last semester, a follow-up analysis was performed with questions on the significance of the completed curriculum for current and future professional challenges regarding digital health and suggestions for improvement for innovative teaching. The study was meticulously planned and supported by an approved ethics vote of the local ethics committee to ensure that all ethical guidelines were adhered to (A 2022-0137). ResultsA total of 20 students participated, with 13 (65%) being women. In particular, data protection and information security were considered the most relevant topics both before and after the curriculum. Significant increases in perceived importance were observed for messenger apps (mean increase of 0.8 [SD 1.2]; P<PPP ConclusionsThe results highlight the potential to integrate more innovative teaching techniques, such as gamification, augmented reality, virtual reality, and simulation training, into a technologically advanced health care environment. Finally, the overarching importance of artificial intelligence and digital health applications signals the need to further integrate them, given their potential in remote and personalized medicine.